Evaluation of the Serologic Cross-Reactivity between Transmissible Gastroenteritis Coronavirus and Porcine Respiratory Coronavirus Using Commercial Blocking Enzyme-Linked Immunosorbent Assay Kits - Ronaldo Magtoto (American Society for Microbiology, 2019)
ABSTRACT This study compared the performances of three commercial transmissible gastroenteritis virus/porcine respiratory coronavirus (TGEV/PRCV) blocking enzyme-linked immunosorbent assays (ELISAs) using serum samples (n = 528) collected over a 49-day observation period from pigs inoculated with TGEV strain Purdue (n = 12), TGEV strain Miller (n = 12), PRCV (n = 12), or with virus-free culture medium (n = 12). ELISA results were evaluated both with “suspect” results interpreted as positive and then as negative. All commercial kits showed excellent diagnostic specificity (99 to 100%) when testing samples from pigs inoculated with virus-free culture medium. However, analyses revealed differences between the kits in diagnostic sensitivity (percent TGEV- or PRCV-seropositive pigs), and all kits showed significant (P < 0.05) cross-reactivity between TGEV and PRCV serum antibodies, particularly during early stages of the infections. Serologic cross-reactivity between TGEV and PRCV seemed to be TGEV strain dependent, with a higher percentage of PRCV-false-positive results for pigs inoculated with TGEV Purdue than for TGEV Miller. Moreover, the overall proportion of false positives was higher when suspect results were interpreted as positive, regardless of the ELISA kit evaluated. IMPORTANCE Current measures to prevent TGEV from entering a naive herd include quarantine and testing for TGEV-seronegative animals. However, TGEV serology is complicated due to the cross-reactivity with PRCV, which circulates subclinically in most swine herds worldwide. Conventional serological tests cannot distinguish between TGEV and PRCV antibodies; however, blocking ELISAs using antigen containing a large deletion in the amino terminus of the PRCV S protein permit differentiation of PRCV and TGEV antibodies. Several commercial TGEV/PRCV blocking ELISAs are available, but performance comparisons have not been reported in recent research. This study demonstrates that the serologic cross-reactivity between TGEV and PRCV affects the accuracy of commercial blocking ELISAs. Individual test results must be interpreted with caution, particularly in the event of suspect results. Therefore, commercial TGEV/PRCV blocking ELISAs should only be applied on a herd basis.